EP811 A retrospective study regarding the role of cytoreductive surgery (CRS) and hypertermic intraperitoneal chemotherapy (HIPEC) in patients with advanced ovarian, fallopian tube or primary peritoneal cancer. (1st November 2019) - Capilna, ME; Moldovan, B; Rad, C; Moldovan, AA; Cozlea, AL
Abstract : Introduction/Background: Emphasizing that complete CRS and HIPEC has potential benefits in patients with ovarian, fallopian tube or primary peritoneal cancer in advanced stages, presenting the morbidity and the oncologic results compared to the traditional surgical debulking combined with conventional intravenous platinum and taxane-based chemotherapy Methodology: A retrospective study was conducted between June 2013–April 2019 including 110 patients, with a mean age of 53.94 years old, who benefited from CRS and HIPEC for primary or recurrent peritoneal carcinomatosis. Results: Upfront CRS and HIPEC was performed in 18 patients (16.36%), while interval surgery and HIPEC was considered in 29 subjects (26.36%). Consolidation CRS and HIPEC was performed in 31 patients (28.18%), while salvage procedure was necessary in 26 patients (23.63%). Six patients (5.45%) required a second CRS and HIPEC. Total peritonectomy following Sugarbaker technique was performed in all patients; large intestine resections were performed in 52 patients (47.27%), small intestine resections in 17 (15.45%), splenectomy in 40 (36.36%), liver resections in 12.72% and diaphragmatic resections in 15.45%. A microscopically cytoreduction (CC0) was achieved in 69 patients (62.73%), macroscopic cytoreduction (CC1) in 36 subjects (32.73%), while gross tumor debulking was performed in 5 (4.54%). Seven patients (6.36%) needed reoperation for postoperative complications. HIPEC was performed using single platinum agents in 30 patients (27.27%), Doxorubicin in 31 (28.18%), while Cisplatin-Doxorubicin association was used in 45 subjects (40.90%), Cisplatin-Mitomicine or Mitomicine alone being applied in smaller percentages. Fifteen patients died from the disease (13.64%), 20 patients are alive with recurrence (18.18%) and 75 are disease free (68.18%), and despite the short follow-up period, survival outcomes are relevant. Conclusion: Extensive CRS followed by HIPEC is a promising therapeutical option in patients with peritoneal carcinomatosis related to gynecological malignancies. Disclosure: Nothing to disclose.